An efficient Jaya algorithm with Powell's Pattern Search for optimal power flow incorporating distributed generation. Issue 8 (3rd August 2021) - Gupta, Saket; Kumar, Narendra; Srivastava, Laxmi
ABSTRACT: Optimal power flow solutions are required for the cost-effective operation and control of an existing power system as well as for its future expansion planning. In this paper, a hybrid meta-heuristic Jaya-Powell's Pattern Search method is proposed to solve the optimal power flow problem integrated with distributed generating units. Powell's Pattern Search method has been incorporated into the Jaya algorithm in three different ways, resulting in three variants namely; Jaya-PPS1, Jaya-PPS2, and Jaya-PPS3. Performance of these variants are evaluated by solving optimal power flow in IEEE 30-bus, IEEE 57-bus, and IEEE 118-bus systems. In all the cases, Jaya-PPS1 is found to provide a lower objective function value with a smaller deviation over multiple runs than other algorithms. For example, the combined objective function found by Jaya-PPS1 for IEEE 30-bus system is 937.340, with a reduction of 2.86% of the original system. This benefit increases further with system size.